The potential of grated Cocos nucifera L. as bio-composite using physico-chemical analysis / Mohamad Firdaus Mohamad Maswan - Mohamad Maswan, Mohamad Firdaus (2015)
Bio-composites is a term used to define reinforcement of biopolymers or synthetic polymers with natural or bio-fiber. Bio-composite product is an environmental friendly and the use of bio-composite is an alternative to decrease pollution. The study of grated Cocos nucifera may provide information for an alternative to nonrenewable natural resources and to solve the problems of plastic waste management. Through this study, the physico-chemical components of grated coconut identified are moisture content (2.36%), turbidity content (65.28%), lignin content (5.28%), holocellulose content (3.92%), a-cellulose content (4.04%) and hemicellulose content (0.13%). Currently, there is no standard or control to compare bio-composite properties. Therefore, this physico-chemical data was compared to establish commercially available bio-composite products. The physico-chemical analysis revealed that the grated coconut has the potential as bio-composite because its physical and lignin analysis showed that grated coconut are comparable to hemp fiber. However, the cellulose content which are a-cellulose, holo-cellulose and hemicellulose content showed otherwise. As a conclusion, there is the potential of grated coconut as bio-composite. However, further study is needed to identify the type of product suitable to be used with grated coconut as reinforcement and to determine its strength.